Development of meat products for the nutrition of the elderly - Sholpan Abzhanova; Lyazzat Baybolova; Gulshat Zhaksylykova; Aigul Tayeva; Talgat Kulazhanov (Human Nutrition & Metabolism, 2023)
Purpose: Due to the increased risk of diseases and digestive disorders, a balanced diet for the elderly is necessary for their well-being and health. Understanding the effects of meat consumption is especially important for older adults, who can benefit from whole-food protein to compensate for age-related loss of muscle mass and strength. The purpose of this study is to analyse the production of meat products and establish the effect of ostrich meat in the nutrition of the elderly. Methods: The theoretical basis of this study included conclusions and basic recommendations from researchers who explore elderly nutrition, and data from the World Health Organization and the Ministry of Health of the Republic of Kazakhstan. Moreover, research on the nutritional value of ostrich meat pate as a possible component of the diet was conducted, and beef pate was used as a control sample. Results: The study found that ostrich meat pate has a high nutritional value and lower caloric content compared with beef pate, with high protein content and low-fat content. In addition, ostrich pate is very valuable for its content of fatty acids: arachidonic, linoleic, linoleic, and oleic. Conclusion: The findings of the study allow to state that ostrich meat is a dietary and low-calorie product that can be recommended for the elderly. The practical value of the study lies in the optimisation of data on the development of meat products for the nutrition of the elderly and the possible inclusion of ostrich meat in the diet.